DETERMINAN MANEJEMEN LABA: PERAN LIABILITAS PAJAK TANGGUHAN DAN LEVERAGE - Eky Septiawan; Yohan H Wibowo; Hendryadi Hendryadi (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2020)
This study aims to provide empirical evidence regarding the effect of deferred tax liabilitie and corporate leverage on earnings management. The object of research is companies included in the LQ45 index listed on the Indonesia Stock Exchange in the period 2014-2018. Hypothesis testing uses panel data regression with the help of the EVIEWS program. The test results show that the deferred tax liabilities have no significant effect on earnings management, while leverage is proven to significantly affect earnings management. The practical implications and suggestions outlined in the article.